,,Pije Kuba do Jakuba”… What did Poles sing at the table in the 19th and early 20th centuries? - Fink, Kinga (Perspektywa stołu, 2023)
The study is devoted to the investigation of the genesis of one of the most popular cantos among Poles in the 19th and early 20th centuries, sung during revels, feasts and social gatherings, and its functioning in social circles. The sources for the study are handwritten theatrical pieces from the Library of the Lviv Theatre, diaries and reminiscences, Polish songbooks published in the 19th and early 20th centuries, and etnohgraphic material from the whole of pre-partition Poland collected by Oskar Kolberg.